Pensar la acción colectiva en el contexto de la logística humanitaria: las lecciones del sismo de Pisco - Chandes, Jérôme (2009)
In the last fifteen years, and increasingly every day, humanitarian logistics has awakened the interest of researches in the logistics and supply chain management (SCM) field. Some consider this is a new area to apply methods and management tools developed in the business area. Researches in humanitarian logistics tend to favor a technical approach, particularly in operational management (transport optimization, location of regional centers, etc.). Although this view is still valid regarding improvement in using scarce logistics resources, this must be associated to organizational methods that seek the best way to coordinate within humanitarian supply chains. The present article assumes this position upon the concept of collective strategy and how it was applied to the earthquake disaster in Pisco, Peru (August 15, 2007). The humanitarian aid was distributed among several disaster aid committees, but above all to the Instituto Nacional de Defensa Civil (Indeci), the state organization that supervised the whole system. Indeci’s management emphasized the importance of collective action to improve the humanitarian aid operation, but it also viewed the difficulties that resulted from this action.